2014
DOI: 10.1111/nmo.12384
|View full text |Cite
|
Sign up to set email alerts
|

Standardized herbal treatments on functional bowel disorders: moving from putative mechanisms of action to controlled clinical trials

Abstract: Symptom relief in functional gastrointestinal disorders (FGID) is frequently sought with complementary and alternative medicine, and various herbal medicine compounds are popular in different parts of the world. Only a few products, however, are standardized and are backed by scientific evidence. This review mainly focuses on mechanistic and clinical data in support of the Japanese traditional compound Rikkunshi-to (RKT) and of STW-5. Their effects on gut sensori-motor function, neurohormonal network, and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…HMs have been reported to produce a synergy of therapeutic effects, e.g. spasmolytic, tonicizing, carminative, anti‐inflammatory and local analgesic …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HMs have been reported to produce a synergy of therapeutic effects, e.g. spasmolytic, tonicizing, carminative, anti‐inflammatory and local analgesic …”
Section: Discussionmentioning
confidence: 99%
“…It also exhibits anti‐stress effects by attenuating the hypothalamic–pituitary‐adrenocortical axis and sympathetic activation. Besides, It was also effective for the extra‐gastric symptoms of patients with FD or IBS, such as dizziness, coldness in the lower extremities, or general fatigue …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Met-analysis mode of research has shown that the mentioned syrup has been effective in removing symptoms of GERD (53,54). The other plant is Myrtus communis L. a pharmaceutical dosage form of Myrtus communis L. (myrtle) was compared with omeprazole and it showed the same efficacy in relieving the GERD symptoms (28).…”
Section: Discussionmentioning
confidence: 98%